A new species of Bothrops (Serpentes: Viperidae: Crotalinae) from Pampas del Heath, southeastern Peru, with comments on the systematics of the Bothrops neuwiedi species group - Carrasco P.A. (2019)
We describe a new species of pitviper of the genus Bothrops from the Peruvian Pampas del Heath, in the Bahuaja-Sonene National Park. Pampas del Heath is an area of seasonally flooded savannas and a northwestern extension of the Gran Chaco Boliviano-Paraguayo.